STUDI MODUL WIFI DAN SIMULASI JARINGAN IEEE 802.11AX PADA SIMULATOR NS-3 UNTUK PENGUKURAN THROUGHPUT - Maulana, Aldias Henry; Wellem, Theophilus (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2024)
IEEE 802.11ax WiFi 6 is the current standard for wireless local area network (WLAN) technology which is a development of the previous standard, namely IEEE 802.11ac (WiFi 5). WiFi 6 has new features that are superior to WiFi 5. For example, it can operate in the 6 GHz frequency band, use 1024-QAM modulation, and use a maximum of 8 spatial streams. In general, to test and verify the implementation of a network technology standard, researchers can buy hardware on the market that has implemented the standard in its entirety or only certain mandatory features. Apart from using hardware directly, testing can also be done using software simulations. This research aims to study the WiFi model in the ns-3 simulator and simulate the IEEE 802.11ax WiFi 6 network. The simulation is carried out to measure the uplink throughput that can be achieved by WiFi 6 with various numbers of client stations (STA) and various distances between the Access Point (AP) and STA. The simulation results show that the throughput value will decrease with increasing AP-STA distance and the number of STA. The maximum throughput value obtained in the simulation with 5 STA at a distance of 2 meters from the AP is 655.41 Mbps.